Analysis of numeracy literacy ability of grade XII students in solving AKM questions on trigonometry - Rahmawati, Andini; Farwati, Serlin; Muthia, Shahla Naila (Pi Radian: Journal of Mathematics Education, 2023)
The Indonesian government adopted a new policy for the education system to improve the quality of education. One of the policies implemented is the elimination of the National Examination, which is a tool for assessing student learning outcomes at the end of each level of education against national standards. The National Examination was replaced with a Minimum Competency Assessment (AKM) and Character Survey. AKM focuses on students' abilities in reading and writing or known as literacy and numeracy. Numeracy literacy includes understanding mathematical concepts and the ability to apply these concepts in everyday life. Trigonometry material. This is an important topic in mathematics that involves the relationship between angles and side lengths of a triangle. Therefore, this research was conducted to analyze the numeracy literacy skills of class The research method used is descriptive qualitative research. The research results showed that the numeracy literacy skills of students in the low category were 40%, in the medium category were 47%, and in the high category were 13%.